2005
DOI: 10.1007/s00420-005-0068-1
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a self-administered questionnaire for assessing exposure to back pain mechanical risk factors

Abstract: Objective: To validate a self-administered questionnaire assessing exposure to mechanical risk factors, developed for a cohort study aiming at assessing the influence of physical and psycho-social factors on the incidence of low back pain (LBP). Methods: The study first involved a criterion validity test. A sample of the cohort workers (n=152) was observed at the workplace during four 30 min periods randomly distributed along the shift. At the end of the work shift, the questionnaire was filled in both by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…Our results showed substantially better agreement between job-title based exposure estimates and observed exposures than for self-reported physical exposures. Generally, past studies report less precise exposure estimates from self-reported data,42–44 although worker self-reported ratings have shown more accuracy with forceful tasks 45…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed substantially better agreement between job-title based exposure estimates and observed exposures than for self-reported physical exposures. Generally, past studies report less precise exposure estimates from self-reported data,42–44 although worker self-reported ratings have shown more accuracy with forceful tasks 45…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that employee reporting of occupational injury using institutional mechanisms is low 26,27 and selfreport of employee occupational health outcomes using survey methods has been validated. 28 Therefore, we directly asked respondents their history of occupational injury and absences in the last 4 months. This recall period was chosen because these are somewhat rare events, but the longer the period, the more likely a respondent is to underestimate the occurrence.…”
Section: Nursing Outcomesmentioning
confidence: 99%
“…5 There have been many studies evaluating the validity and reliability of self-reported surveys to assess physical exposures that attribute to disorders of the low back, lower extremity and upper extremity. 6 In validity studies, self-reported surveys are often compared to reference methods such as direct observation, [7][8][9] observed videotaped work samples, 3,10 and direct measurement. 11,12 Survey items vary by study addressing issues such as the types of tasks (walking sitting), the characteristics of the exposures (time, intensity, body posture) and the associated injury risks.…”
Section: Introductionmentioning
confidence: 99%